287th ENMC international workshop: Harmonization and federated analysis of myotonic dystrophy registries to model heterogeneous disease trajectories. Hoofddorp, the Netherlands, 28–30 March 2025 - la Fontaine, Leandre A.; van As, Daniël; Bassez, Guillaume; Johnson, Nicholas E.; Faber, Catharina G.; Hoen, Peter A.C.’t (Neuromuscular disorders : NMD, 2026)
•Achieved consensus on expanding the core dataset: The workshop led to a unanimous agreement on updating the core dataset of DM registries to incorporate both clinical and patient-reported outcomes.•Developed strategies for FAIR data integrating: participants outlined actionable strategies to ensure that data integration aligns with FAIR principles, promoting data sharing and collaboration across registries.•Proposed governance models for federated analysis: The workshop provided governance models to support federated analysis, and provided strategies for future analyses to support post-marketing surveillance. The 287th ENMC International Workshop convened experts from ten countries to address the harmonization and federated analysis of Myotonic Dystrophy Type 1 (DM1) registries. With over 10,500 patients enrolled globally, registries remain fragmented, limiting their utility in modeling disease trajectories and supporting clinical trials. As new therapies enter advanced clinical testing, registries must evolve - not only to enable trial readiness but also to support downstream functions like pharmacovigilance. The workshop focused on four objectives: re-defining a core dataset, enabling FAIRification of registries, establishing federated analysis infrastructure, and developing longitudinal modeling strategies. Key outcomes included a revised core set of clinical and patient reported outcome measures that is feasible to collect in a routine care setting, strategies for FAIR data integration, and governance models for federated analysis. Pragmatic and interpretable statistical approaches such as latent variable modeling and unsupervised clustering were discussed, with key prediction targets identified across motor, cardiac, and pulmonary domains. The workshop emphasized the need for sustainable funding, patient-centered design, and international collaboration.